Differential impact of microcystins MC-LR and [D-Leu1]MC-LR in different areas of the rat brain after chronic exposure: oxidative stress and antioxidant responses - Hernando, Marcelo Pablo (2025)
Cyanotoxins are a significant concern due to their frequent presence in Southamerica waters. While numerous studies have investigated the toxic effects of MC-LR, knowledge regarding the toxicity of [D-Leu1]MC-LR remains limited. The aim of this study was to determine the impact of [D-Leu1]MC-LR and MC-LR administration on different brain structures in rats and the resulting modifications in oxidative stress. Male Sprague-Dawley rats were divided into two groups and administered 5 intraperitoneal injections of mixed MCs at doses of 2 and 15 μg kg1 for each injection over a 21-day period, i.e. total doses of 10 and 75 μg kg1.The MCs consisted on MC-LR (3 %), [D-Leu1]MC-LR (96.7 %) and others (0.3 %) isoforms. To evaluate the effect of treatments with different doses, the concentration of both MC isoforms, reactive oxygen species (ROS), lipid damage and antioxidant activity were measured in the cerebral cortex, hippocampus, striatum and cerebellum. The results revealed variability in MC concentration across brain regions. The accumulation rate of MC-LR was 2000 times higher than that of [D-Leu1]MC-LR, regardless of the dose administered at different areas. Taken together, our results highlighted that chronic exposure to MCs induced a mild oxidative stress in the rat brain characterized by increased ROS and antioxidant defense activation due to [D-Leu1]MC-LR in both the striatum and cortex at high dose. At low dose, the uptake of only MC-LR was determined in the cerebellum and hippocampus, resulting in increased ROS levels but no change in CAT activity in the hippocampus. In contrast, in the cerebellum, there was a decrease in ROS, possibly due to increased CAT consumption. However, the absence of detection of an MC variant under certain conditions does not allow for the exclusion of its metabolic effects. Chronic MC administration resulted in dose- and region-dependent distribution within the rat brain. Reactive species levels and cellular responses also varied by dose and region.